An Illoucutionary Astcs In Jesus’ Conversation In The Gospel Of Mark - Wereh, Oktavianus; Tuerah, Ignatius J. C.; Andries, Fivy (Program Studi Pendidikan Bahasa Inggris, 2025)
This study aims to identify illocutionary acts in Jesus' conversations with the people and His disciples in the New Indonesian Translation of the Gospel of Mark, and to explain the contextual meaning of these illocutionary acts. This study uses a qualitative approach with a documentation method, where data is collected through text analysis of the New Indonesian Translation of the Gospel of Mark. This method was chosen because it is in accordance with the aim of understanding the illocutionary acts contained in Jesus' conversations, which are expressed through His words and statements. The results of the study show that Jesus often uses assertive illocutionary acts in expressing truths about the Kingdom of God, forgiveness of sins, and moral teachings. These acts can be found in various parts of the Gospel of Mark, such as statements about repentance and faith delivered by Jesus to the people (Mark 1:15), as well as His teachings about humility, sacrifice, and the importance of inner purity. In Mark’s Gospel, Jesus also uses illocutionary acts to affirm that true greatness lies in service and sacrifice (Mark 9:35, 10:45), and to teach that worldly values, such as wealth, can hinder one’s spiritual journey (Mark 10:23-25). These statements show how Jesus provides a new understanding of holiness, relationship with God, and the moral principles His followers should uphold.